PEMBUATAN SISTEM INFORMASI ADMINISTRASI ORGANISASI MAHASISWA UNIVERSITAS SURABAYA - Fony Rosiana; Dhiani Tresna Absari; Fitri Dwi Kartikasari (CALYPTRA, 2018)
University of Surabaya (Ubaya) is one of the private universities in Surabaya, East Java. In general, any university that is both private and state universities have student organizations in accordance with the interests of each university. Similarly, the University of Surabaya. At present, the administrative activities that include recording and realization of the activities of the work program is still running it manually. Processes running manually is a time consuming, because there are several steps that must be done in a way to meet people. The duration of the administration process can impede the course of events. Therefore, making this system aims to help the administration process so that the process can be completed more quickly and does not inhibit the activity. Analysis of system requirements through interviews to the parties concerned and also made observations on the course of the administrative process. This system will streamline administrative processes and activities can save the file with the existing format seminimalis system design made possible so it does not make the user confused in using this system. The system is made by using CodeIgniter and phpMyAdmin. After going through the process of testing, the system created to help according to the needs of student organizations University of Surabaya. Final conclusion of this system can help reduce errors and help accelerate the process of administrative activities.